Neuroprotective Activity of Water Soluble Extract from Chorispora bungeana against Focal Cerebral Ischemic/Reperfusion Injury in Mice - Ya-Xuan Sun; Ting Liu; Xue-Ling Dai; Ya-Bo Li; Yu-Yao Li; Hua Zhang; Li-Zhe An (Journal of Chemistry)
The purpose of the present study was to clarify whether the water extract of Chorispora bungeana was an antioxidant agent against cerebral ischemia/reperfusion (I/R). Our results showed that water extract of Chorispora bungeana treatment significantly reduced neurological deficit scores, infarct size, MDA and carbonyl contents, and GSH/GSSG ratio compared with the model control group. After being treated by Chorispora bungeana, SOD, CAT, and GSH-Px activities remarkably increased. Chorispora bungeana treatment also improved 8-OHdG expression and cell apoptosis. Our findings indicated that the water extract of Chorispora bungeana possesses neuroprotective effect which is most likely achieved by antioxidant and antiapoptotic activities.